2018
DOI: 10.1088/1674-4926/39/4/042001
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of structural, electronic and magnetic properties of SnGe n (0, ±1) ( n = 1–17) clusters

Abstract: The structures, relative stability and magnetic properties of pure Ge n+1 , neutral cationic and anionic Sn-Ge n (n = 1-17) clusters have been investigated by using the first principles density functional theory implemented in SIESTA packages. We find that with the increasing of cluster size, the Ge n+1 and SnGe n (0, ±1) clusters tend to adopt compact structures. It has been also found that the Sn atom occupied a peripheral position for SnGe n clusters when n < 12 and occupied a core position for n > 12. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
3
0
3
Order By: Relevance
“…Phương pháp phiếm hàm mật độ (DFT) được nhiều nhà khoa học sử dụng nhằm dự đoán cấu trúc, độ bền và tính chất electron của cácclusters kim loại [3,10,15,16]. Trong nhiều phiếm hàm đopược sử dụng đối với phương pháp DFT thì phiếm hàm BP86 [17] kết hợp với bộ hàm cơ sở LANL2DZ [18][19][20] tỏ ra đạt được kết quả tốt có độ tin cậy cao, phù hợp với các giá trị thực nghiệm khi áp dụng cho việc tính toán cấu trúc các cluster kim loại chuyển tiếp được chọn trong các bài báo này [21,22].…”
Section: Phương Pháp Tínhunclassified
“…Phương pháp phiếm hàm mật độ (DFT) được nhiều nhà khoa học sử dụng nhằm dự đoán cấu trúc, độ bền và tính chất electron của cácclusters kim loại [3,10,15,16]. Trong nhiều phiếm hàm đopược sử dụng đối với phương pháp DFT thì phiếm hàm BP86 [17] kết hợp với bộ hàm cơ sở LANL2DZ [18][19][20] tỏ ra đạt được kết quả tốt có độ tin cậy cao, phù hợp với các giá trị thực nghiệm khi áp dụng cho việc tính toán cấu trúc các cluster kim loại chuyển tiếp được chọn trong các bài báo này [21,22].…”
Section: Phương Pháp Tínhunclassified
“…4. In the general trend of the curves, it is observed that they present oscillations and very prominent peaks at the range sizes n  2, 4, 7, 10, 12, 14, and 19 atoms for SiGen and at n  2, 3,5,6,8,11,12,13,15, and 20 for Gen + 1. This indicates that these clusters are more stable than the others.…”
Section: Second-order Difference δ2ementioning
confidence: 92%
“…They figured out that the replacement of one Ge atom by a Cu one improved the stabilization of germanium clusters compared to Ag and Au. Djaadi et al [8] have considered the magnetic properties and relative stability of pure and tin-doped germanium clusters SnGen (0, ±1) (n  1-17). This attempt resulted that these clusters took compact geometries as the cluster size magnified.…”
Section: Introductionmentioning
confidence: 99%
“…Phương pháp phiếm hàm mật độ (DFT) được nhiều nhà khoa học sử dụng nhằm dự đoán cấu trúc, độ bền và tính chất electron của các cluster kim loại [3,5,6,9]. Trong nhiều phiếm hàm trao đổitương quan được sử dụng đối với phương pháp DFT thì phiếm hàm PBE (Perdew-Burke-Ernzerhof) [10] tỏ ra đạt được kết quả tốt, có độ tin cậy cao, phù hợp với các giá trị thực nghiệm cho các hệ cluster của germanium [11][12][13][14][15]. Vì vậy, tất cả các tính toán thực hiện tối ưu hình học, tần số dao động và năng lượng của các cấu trúc trong nghiên cứu này sử dụng phiếm hàm PBE kết hợp với bộ hàm cơ sở hóa trị tách ba của Pople có bổ sung các hàm phân cực và khuyếch tán, 6-311+G(d) [16], thông qua phần mềm Gaussian 09 [17].…”
Section: Phương Pháp Tínhunclassified